Marine Bacteria Is the Cell Factory to Produce Bioactive Pigments: A Prospective Pigment Source in the Ocean - Velmurugan, Palanivel; Venil, Chidambaram Kulandaisamy; Veera Ravi, Arumugam; Dufossé, Laurent (Frontiers in Sustainable Food Systems, 2020)
The course of investigations of bioactive compounds like bacterial pigments from the marine environment has greatly expanded in the recent decades. Despite the huge concern in secluding and collecting marine bacteria, microbial metabolites are progressively alluring to science due to their wide ranging applications in various fields, particularly those with distinctive color pigments. This review is a short appraisal of the studies undertaken over the past 5 years on the bacterial pigments sourced from the marine environment. Herein, we have reviewed the potential of different bacterial species isolated from marine environment in diverse studies that are producing bioactive pigments that have potential commercial applications.